Pengaruh Sistem Pengendalian Internal dan Pengawasan Keuangan Daerah terhadap Keandalan Penyajian Laporan Keuangan Pemerintah Daerah (Studi Kasus pada Satuan Kerja Perangkat Daerah Kabupaten Sikka) - Helena Adventy Gudipung; Konstantinus Pati; Yoseph Darius Purnama Rangga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aimed to investigate the impact of the Internal Control System and Regional Financial Supervision on the Accuaracy of the Financial Reports of the Sikka Regency Regional Government. The research follows an associative approach with a causal relationship form and utilizes a quantitative method. The population and sample for this research include all Regional Apparatus Work Units (SKPD) in Sikka Regency. Data was collected through a questionnaire distributed to each SKPD, with a total of 72 respondents. The data analysis involved multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS). This research showed that the significance value of X1 is 0.004, which is lower than the significance level of 0.05 (0.004<0.05) with a t-value of 2.989. Similarly, the significance value of X2 is 0.000, also lower than the significance level of 0.05 (0.000<0.05) with a t-value of 4.365. Additionally, the F-test yields a significance vale of 0.000, which is less than the specified significance level of 0.05 (0.000<0.05) with an F-value of 36.690. Therefore, it can be concluded that both the Internal Control System and Regional Financial Supervision significantly impact the Reliability of Financial Report Presentation, both individually and simultaneously.